DETERMINAN NILAI SEWA BILLBOARD DI KABUPATEN SLEMAN - , Fransiscus Raja Doly ([Yogyakarta] : Universitas Gadjah Mada, 2013)
This research aimed to identify the determinants of rental value of billboards in Sleman and compile them in a rental billboard valuation models. The reasearch used cross section data obtained by interviewing with 13 advertising company and included 74 observation scattered in various locations in Sleman. Secondary data such as the realization of advertisement tax and zoning classifications derived from Dinas Pendapatan Daerah Kabupaten Sleman. Multiple linear regression analysis with Ordinary Least Square method was used to measure the influence of the determinant such as lot size, type of billboard, duration of contract and location of billboards to rental value of billboard. Log-log model was chosen as the best estimation model with coefficient of determination (R2) was about 88,73 percent which means that the 88.73 percent behavior of the dependent variable was able to be explained by the independent variables. The economic, statistic and econometric test showed that lot size, type of billboard and location influenced positively the rental value of billboard meanwhile the duration of contract had negative relation to rental value of billboard.